Visualization and Modeling of the In Vivo Distribution of Mesenchymal Stem Cells - Wang, H.; Thorling, C.; Xu, Z.; Crawford, D.; Liang, X.; Liu, Jian; Roberts, M. (2017)
Copyright © 2017 John Wiley & Sons, Inc. This unit describes a protocol for elucidating the in vivo disposition of administered mesenchymal stem cells (MSCs). Specifically, direct visualization of donor cell spatiotemporal distribution and assessment of donor cell quantity in recipient organs are described. Protocols for data analysis are suggested, with the goal of developing a model to characterize and predict the physiological kinetics of administered MSCs. The use of this model is described, suggesting that it can be applied to abnormal conditions and has potential interspecies and inter-route predictive capability. These universal methods can be employed, regardless of the type of stem cell or disease, to guide future experiments and design treatment protocols. © 2017 by John Wiley & Sons, Inc.